High-efficiency, compressible, and recyclable reduced graphene oxide/chitosan composite aerogels supported g-C3N4/BiOBr photocatalyst for adsorption and degradation of rhodamine B. Issue 2 (April 2022) - Pan, Hongyang; Gu, Jiamin; Hou, Kaiyang; Li, Junyao; Wang, Yu; Yue, Yiying
Abstract: Photocatalytic technology has received considerable attention due to its advantages of high efficiency, economy and thorough degradation of pollutants, making it the most promising sewage treatment technology. However, the difficulty in recycling usually limits its applications. In our research, we developed a composite aerogel with excellent mechanical properties, photocatalytic properties and recyclability to adsorb and degrade rhodamine B (RhB) dye. In this composite, g-C3 N4 /BiOBr was loaded on the matrix of rGO and chitosan (CS), with borax as the crosslinking agent. The adsorption experiment showed that the equilibrium adsorption capacity of g-C3 N4 /BiOBr@CS/rGA aerogels were 3.08 mg/g. The composite photocatalyst of g-C3 N4 /BiOBr could effectively inhibit the recombination of photo-generated carriers, loaded on the rGO matrix with admirable conductivity, which further improved the photocatalytic performance. The degradation rate of RhB could reach to 94.6% at 180 min under the neutral condition of pH= 7. In addition, the amine group of CS reacted with the carboxyl group of GO to form an amide group, it enhanced the mechanical properties of the aerogels. The compressive strength was 0.152 MPa at 50% strain, and there was basically no decrease after 5 cycles. The composite aerogels exhibited good recycling performance, and the degradation rate was about 80% after 4 cycles. Graphical Abstract: ga1 Highlights: g-C3 N4 /BiOBr@CS/rGA was prepared to realize the recycling of photocatalytic materials. rGO matrix with good conductivity could transfer the photogenerated electrons. The cross-linking of CS and GO enhanced the mechanical properties of aerogels. g-C3 N4 /BiOBr acted as not only a photocatalyst but also a reinforcing agent. The union of g-C3 N4 and BiOBr inhibited the recombination of photogenerated carriers.